diffrential
posted by armut .
show that s(t)=exp(kt) can be written in the form s(t)=2^(kt/ln(2))

since 2 = e^ln2
e^(kt) = e^(ln2 * kt/ln2)
= (e^ln2)^(kt/ln2)
= 2^(kt/ln2)
Respond to this Question
Similar Questions

Physics/Math
A can of sardines is made to move along an x axis from x1 = 0.2 m to x2 = 1.2 m by a force given by F = iF0exp(0.4x), with x in meters and F0 = 4.5 N. (Here exp is the exponential function.) How much work is done on the can by the … 
(expi)^i
This question is not well defined. By 'expi' do you mean exp(i)? 
Calculus II
What is sin(i)  (sin of the imaginary number, i) What is cos(i) cosine of the imaginary number, i orrr tan(1+i) You can derive these things from the equation: Exp(i x) = cos(x) + i sin(x) > sin(x) = [Exp(ix)  Exp(ix)]/(2i) … 
mathscomplex numbers
by using the substitution w = z^3, find all the solutions to z^6  8z^3 +25 = 0 in complex numbers, and describe them in polar form, using @(theta) to denote the angle satisfying tan@ = 3/4 ( note simply leave @ as it is, don't calculate … 
Math/Calculus
How would I evaluate the following integral by using integration by parts? 
calc: arc length
find the exact length of this curve: y = ( x^3/6 ) + ( 1/2x ) 1/2 <or= x <or= 1 im looking over my notes, but i'm getting stuck. here's my work so far: A ( 1 , 2/3 ) B ( 1/2 , 49/48 ) y' = [1/6 (3x^2)] + [1/2 (1x^2)] y' = ( … 
Maths
Transform the following relationships/funtions into linear form and identify expressions for the x and y variables. a) (x^2/a^2) + (y^2/b^2) = 1 where a and b are constants. b) k(T) = (kT/h)exp((deltaS)/R)exp((deltaH)/RT) where k, … 
Maths
P=(2J+1)exp((BJ(J+1))/kT) where B, k and T are constants a. Show that dP/dJ=(2(B(2J+1)^2)/kT)exp(BJ(J+1)/kT) b. Show that P exhibits a maximum and determine the expression for Jmax c. Find the value of P when J=0 and the limiting … 
geography
What is unusual about the written form of the Chinese language? 
diffrential equations
Find two linearly independent power series solutions to the diffrential equation. State the first 3 therms of each series: 2x^2y''+xy'(1+2x^2)y=0